189 DEVELOPMENT OF A HIGH SENSITIVITY, HIGH THROUGHPUT SCREEN FOR NEUROINFLAMMATORY RESPONSE USING A MOLECULAR MARKER AND MICROGLIAL ACTIVATION. (1st January 2005) - Sexton, M.; Bornhop, D. J.; Stella, N.; Bai, M.
Abstract : Introduction: Microglial cells are mononuclear macrophage cells unique to the Central Nervous System (CNS). The peripheral benzodiazepine receptor (PBR) is a mitochondrial membrane protein known to be involved in a variety of cellular functions. There is a correlation between upregulated PBR expression and aberrant cell growth, proliferating cancer and neuroinflammation. Purpose: Here we demonstrate the potential for employing a high throughput plate based assay as a screening tool. By targeting the PBR using a fluorescently labeled PBR ligand (RED-PK11195), a plate-based assay was developed using microglial cells labeled with RED-PK and fluorescence was measured in response to various stimuli. Methods: The murine microglial cell line BV2 was cultured and plated in 24 well plates in MEM/Cellgro, incubated over night with various immunomodulatory factors, subsequently rinsed and labeled with the RED-PK dye in PBS. Fluorescence values were measured on a plate reader and PBR expression quantified. As in the past, microglial activity appears to be correlated with PBR expression as quantified using the fluorescent dye. Summary: BV2 cells were capable of being labeled with the RED-PK dye as confirmed with fluorescence microscopy. BV2 cells were capable of producing a change in PBR expression under varying conditions and fluorescence values could be quantified on a plate reader. Conclusions: PBR is a viable target for molecular labeling in microglial cells, providing an indicator of activation status. Potential applications for this high throughput screen using a plate based assay are numerous. Ongoing studies will evaluate the correlation of PBR expression with cytokine, nitric oxide and reactive oxygen species (ROS) production.